2010
DOI: 10.1063/1.3517083
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-modified ferrimagnetism in MnGa films

Abstract: We report the substrate-modified magnetic properties of the CuAu type-I (L10) structure of MnxGa (1.2<x<1.5) films. The magnetic properties of the MnGa films differed greatly due to the influence of the substrate. The MnGa film is a hard ferrimagnet when grown on GaSb (111), becomes a soft ferrimagnet when grown on Al2O3 (0001), and exhibits an absence of a net magnetic moment when stabilized on a GaSb (100) substrate. This difference was attributed to the substrate, which forces MnGa film to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 19 publications
2
28
1
Order By: Relevance
“…In contrast to the epitaxial sample, M(H) of the nanostructured film has a wide "s"-shaped major hysteresis (irreversibility) loop. The coercive field for the nanostructured film is exceptionally large,  o H C = 2.5 T. This is much larger than the coercive field for the epitaxial film,  o H C = 0.36 T, which is typical of other high-quality epitaxial films [11][12][13]15 and bulk samples 6 . The magnetism of nanostructured films is robust with respect temperature.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast to the epitaxial sample, M(H) of the nanostructured film has a wide "s"-shaped major hysteresis (irreversibility) loop. The coercive field for the nanostructured film is exceptionally large,  o H C = 2.5 T. This is much larger than the coercive field for the epitaxial film,  o H C = 0.36 T, which is typical of other high-quality epitaxial films [11][12][13]15 and bulk samples 6 . The magnetism of nanostructured films is robust with respect temperature.…”
mentioning
confidence: 88%
“…Despite the particle-like growth, all of the films had metallic conductivity with longitudinal resistivities in the range ρ = 200 to 300 ·cm, very similar to that measured in epitaxial films. 11,15 Figure 3 shows results of room temperature Hall effect measurements of a 20 nm thick nanostructured Mn x Ga film. In Fig.…”
mentioning
confidence: 99%
“…Moreover, it was reported that the substrate modifies the magnetic properties of L1 0 -Mn x Ga (1.2ox o1.5) films. Particularly, the Mn x Ga film is a hard ferrimagnet when grown on GaSb (111), becomes a soft ferrimagnet when grown on Al 2 O 3 (0001), and exhibits an absence of a net magnetic moment when stabilized on a GaSb (100) substrate [33]. These results may be helpful in modifying magnetic anisotropy in thin films for spintronic applications.…”
Section: Introductionmentioning
confidence: 94%
“…Previous experimental results have shown that the Mn-Ga alloys grown on substrate or in superlattices have affected the tetragonality of the crystal structures, which is attributed to the lattice strain, and this has influence on the magnetic properties and the magnetocrystalline anisotropy of the alloys [18,[30][31][32][33][34][35][36]. It was found that the crystalline orientation of the Ferromagnetic L1 0 -MnGa thin films, which epitaxially grown on GaN, sapphire, and MgO substrates, differ due to the influence of the substrate [32].…”
Section: Introductionmentioning
confidence: 99%
“…The reported coercivities of L1 0 -MnGa films and powders are in the range of 2.2-6.2 kOe, which is not sufficiently high to qualify as a candidate for rare-earth-free magnets. [6][7][8][9][10][11] The D0 22 -Mn 3 Ga intermetallic compound, known as the Al 3 Ti-type MnGa phase, also has a tetragonal structure (I4/mmm). 12 Three different Mn 3 Ga intermetallic compounds are known to exits: the tetragonal D0 22 -Mn 3 Ga intermetallic compound, hexagonal D0 19 -Mn 3 Ga intermetallic compound, and cubic L2 1 -Mn 3 Ga intermetallic compound.…”
Section: Introductionmentioning
confidence: 99%